Fuzzy control for guaranteeing absolute delays in web servers. (2nd May 2007) - Wei, Yaya; Lin, Chuang; Chu, Xiaowen; Voigt, Thiemo
This paper presents a fuzzy control approach that guarantees absolute delays in web servers. Previous work has proposed the use of classical Proportional-Integral (PI) controllers for delay guarantees. However, a disadvantage of the classical PI controller is that the system model, which is obtained by system identification, mismatches the real system and inevitably degrades the performance of the web system. In contrast with classical PI controllers, fuzzy controllers are non-linear and therefore independent of the accurate model of the plant, i.e., the controlled system. Hence, fuzzy controllers seem to be very suitable for web servers. Our experiments show that fuzzy controllers indeed perform better than PI controllers presented in earlier papers.